Intermediate electromagnetic turbulence at comets - Verheest, F.; Lakhina, G.S.; Tsurutani, B.T. (My University, 1999)
Low-frequency electromagnetic turbulence observed in cometary environments mostly peaks at the gyrofrequency of the water-group ions of cometary origin, because of cyclotron resonance fueled by relative drifts parallel to the interplanetary magnetic field. Nevertheless, some of the observations point to pickup proton cyclotron turbulence, to single-cycle magnetic pulses or solitary waves at the proton gyrofrequency, and also to intermediate frequencies between the water-group and the proton gyrofrequencies, The generation of turbulence at such frequencies has been attributed to cascade via wave-wave interactions, but here an alternative and direct mechanism for the generation of these waves is suggested in an unstable wavelength band when the solar wind is sufficiently mass-loaded by cometary material. It is shown, for average parameters near comet 1P/Halley, that unstable modes of the intermediate frequency kind can indeed occur up to several million kilometers from the cometary nucleus and are easier to excite in higher-velocity solar wind flows.
Keywords: Electromagnetic turbulence; Solar wind; Solitary waves